KajianTeknis Pengaruh Panjang Pukulan Terhadap Recovery Pencucian Bijih Timah Menggunakan Alat Pan American Jig Skala Laboratorium Jurusan Teknik Pertambangan Universitas Bangka Belitung - Adiyatma Adiyatma; Janiar Pitulima; Irvani Irvani (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2018)
Washing stage of tin ore is done the separation process valuable minerals of tin ore with mineral impurities. This process can be done using jig such as Pan American Jig. The length of stroke is one of the parameters that affect the performance of the jig with high recovery of tin ore leaching. The experiment was carried out by washing experiment using Pan American Jig scale laboratory on 6 times including variation of stroke length 15 mm, 12 mm, 10 mm, 8 mm, 6 mm, and 5 mm with 19 washing sample. The collection and processing of data includes the weight and grade in each of the feed, concentrates and tailings. Determination of recovery value of each experiment is done through calculation between the grade and weight produced by each sample from washing process. Minerals with a high CC value will be very easily separated by the method of Gravity Concentration for example mineral cassiterite with quartz. The highest recovery was obtained in experiment 1 of 68.848% with a stroke length of 15 mm and the lowest recovery was in experiment 6 of 45.801%. However, the highest grade gain was in experiment 6 of 1.3246% and the lowest grade in experiment 1 was 1.2438%. The higher stroke length made greater recovery value produced, the greater recovery made the lower grade obtained.